Program outcomes monitoring system for civil engineering students (POSCES) - Mohamad Nor, Md Rasul; Ahmad, Hazrina; Juhari, Nurjuhanah; Mohamad Sakdun, Noor Syafeekha; Ismail, Shafienaz; Ismail, Ruqayyah (Universiti Teknologi MARA, Kedah, 2023)
POSCES (Program Outcomes Monitoring System for Civil Engineering Students) is a web-based system that is developed to ease the program outcomes attainment management for the degreeprogram in the Civil Engineering Studies, UiTM Cawangan Pulau Pinang. There are 12 Program Outcomes that are considered in the development of the engineering curriculum, and it is used to strategize the teaching and learning methods throughout the study years. Therefore, the monitoring of these 12 programme outcomes attainment requires an effective system to store, calculate and systematically manage the students’ performance individually as well as according to the student’s intake. Proper data management of the program outcomes are essential to ensure the continual quality improvement (CQI) is implemented throughout the engineering programme. This POSCES system directly engaged the OBE committee of the centre of study, lecturer teaching each course, theacademic advisors, and the students themselves as the primary stakeholder. By using the web-based environment, POSCES is accessible anytime and anywhere, through laptops, tabs, or handphones comfortably by all parties involved. POSCES is considered as a kickstart for the Program Outcome systematic management system that can be applied in various engineering programme across the engineering faculties as well as across higher learning institutions. It is a data management systemthat can be seen as a compulsory for the engineering courses in fulfilling the requirements of the Engineering Accreditation Council (EAC) Engineering Technology Accreditation Council (ETAC).